Identification of peroxidase-1 and beta-glucosidase as cross-reactive wheat allergens in grass pollen-related wheat allergy - Ryohei Ogino (Allergology International, 2021)
Background: Some patients with wheat-dependent exercise-induced anaphylaxis (WDEIA) or wheat allergy showed negative ω-5 gliadin-specific IgE test and high level of grass pollen-specific IgE. It was presumed that these patients developed allergic reaction upon cross-reaction of their IgE antibodies raised against grass pollen allergens to wheat allergens. This study aimed to clarify clinical characteristics and wheat allergens of this phenotype of WDEIA/wheat allergy, which were tentatively diagnosed as grass pollen-related wheat allergy (GPWA). Methods: A total of six patients with GPWA were enrolled, and controls were 17 patients with grass pollen allergy but no episode of wheat allergy, and 29 patients with other wheat allergies: 18 with conventional WDEIA and 11 with hydrolyzed wheat protein allergy. Sensitization to wheat proteins was determined by basophil activation test (BAT). IgE-binding proteins in wheat flour were identified by immunoblotting followed by mass spectrometry. Wheat allergen-specific IgE tests were established by CAP-FEIA system. Results: All the six patients with GPWA were sensitized to water-soluble wheat proteins in BAT and IgE-immunoblotting, and peroxidase-1 (35 kDa) and beta-glucosidase (60 kDa) were identified as specific IgE-binding wheat proteins. The binding of patient IgE to these proteins was inhibited by pre-incubation of patient sera with grass pollen. The peroxidase-1- and beta-glucosidase-specific IgE tests identified three and four of six patients with GPWA, respectively, but only two of 29 controls, indicating high specificity of these tests. Conclusions: Peroxidase-1 and beta-glucosidase are specific wheat allergens for GPWA among grass pollen allergy and other types of wheat-induced food allergies.